2022
DOI: 10.1038/s41598-022-08654-7
|View full text |Cite
|
Sign up to set email alerts
|

Urban noise and surrounding city morphology influence green space occupancy by native birds in a Mediterranean-type South American metropolis

Abstract: Urban green spaces provide natural habitat for birds in urban landscapes, yet the effects of noise and surrounding urban morphology on bird community structure and distribution are not well understood in Latin America, the second most urbanized region in the world. Santiago of Chile is the single city belonging to the Mediterranean ecosystem in South America and is subject to extensive urbanization as seen throughout Latin America. We examined the role of 65 urban green spaces—6 large urban parks (PAR) and 59 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 35 publications
0
6
0
3
Order By: Relevance
“…However, most previous studies have focused on the comparison between urban and rural areas in terms of birdsong. Environmental differences within cities also affect birds’ community structure and distribution, e.g., the differences in the urban morphology (i.e., building height and density) in parks or residential areas [ 15 ]. With the development of urbanization in China, more and more high-rise residential buildings (at least 10–15 stories, with many even over 30 stories) have been constructed in recent years [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous studies have focused on the comparison between urban and rural areas in terms of birdsong. Environmental differences within cities also affect birds’ community structure and distribution, e.g., the differences in the urban morphology (i.e., building height and density) in parks or residential areas [ 15 ]. With the development of urbanization in China, more and more high-rise residential buildings (at least 10–15 stories, with many even over 30 stories) have been constructed in recent years [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, differences within each city might also be related to factors that were not analyzed in this study, including the spatial configuration of the green areas found in these sample sites, such as their size, shape, or their connectivity, or aspects related to the quantity and quality of the habitat they offer [62]. Likewise, factors that characterize the urban matrix in which bird count sites are immersed (e.g., building density or urban noise) could influence limitations in their ability to retain some species [63]. Some research has shown that larger cities with a higher degree of urbanization lose highly specialized groups and maintain species that are ecologically similar to each other, a process known as biotic homogenization [64,65] that would not be supported in Bogotá and Medellín, accompanied by the high levels of complementarity between the sites in each city.…”
Section: Discussionmentioning
confidence: 98%
“…However, differences within each city might also be related to factors that were not analyzed in this study, including the spatial configuration of the green areas found in these sample sites, such as their size, shape, or their connectivity, or aspects related to the quantity and quality of the habitat they offer [62]. Likewise, factors that characterize the urban matrix in which bird count sites are immersed (e.g., building density or urban noise) could influence limitations in their ability to retain some species [63].…”
Section: Discussionmentioning
confidence: 99%
“…However, differences within each city might also be related to factors that were not analyzed in this study, including the spatial configuration of the green areas found in these sample sites, such as their size, shape, or their connectivity, or aspects related to the quantity and quality of the habitat they offer [ 62 ]. Likewise, factors that characterize the urban matrix in which bird count sites are immersed (e.g., building density or urban noise) could influence limitations in their ability to retain some species [ 63 ]. In future studies, such spatial or temporal information should be included as urban covariates to enhance analysis capabilities (i.e., GLMs, GLMMs, or hierarchical models) that allow the identification of the size of this covariates effect and its contribution to explaining some of the bird community patterns found, as already described in other short-term studies in neotropical cities [ 64 66 ].…”
Section: Discussionmentioning
confidence: 99%